Phenotypic Transformation of Liver Macrophages (Kupffer Cells): The Impact of Drug-Induced Immunosuppression on Innate Immunity - Bahodirovna, Shukurova Dilorom; D. E., Jumayeva (American Journal of Biomedicine and Pharmacy, 2026)
Liver macrophages, or Kupffer cells, are pivotal regulators of innate immunity, maintaining hepatic homeostasis and orchestrating inflammatory responses to pathogens, toxins, and cellular stress. Drug-induced immunosuppression, commonly employed in organ transplantation and treatment of autoimmune disorders, profoundly affects Kupffer cell phenotype, leading to altered cytokine production, impaired phagocytic activity, and dysregulation of innate immune responses. This article provides a detailed analysis of the phenotypic transformations of Kupffer cells under chronic immunosuppressive therapy, explores the molecular mechanisms underlying these changes, and evaluates the consequences for hepatic immunity and systemic inflammatory regulation. By examining shifts in macrophage polarization, functional activity, and interaction with other hepatic cell types, this review highlights the implications of immunosuppression on liver immunobiology and proposes potential strategies for mitigating immune dysfunction while preserving therapeutic efficacy. Understanding Kupffer cell dynamics in this context is critical for optimizing patient outcomes, preventing infection, and reducing the risk of immunopathology during long-term pharmacological immunosuppression. Kupffer cells, as liver-resident macrophages, are central regulators of hepatic innate immunity, coordinating responses to pathogens, toxins, and tissue stress. Chronic drug-induced immunosuppression, a cornerstone of organ transplantation and autoimmune therapy, triggers phenotypic transformation of these cells, leading to altered polarization, diminished phagocytic function, and imbalanced cytokine production. This article presents a comprehensive analysis of the cellular and molecular mechanisms underlying Kupffer cell adaptation during prolonged immunosuppressive therapy, emphasizing the consequences for innate immune defense and systemic immune homeostasis. By evaluating shifts in M1/M2 polarization, functional impairment, and intercellular communication, the review highlights how immunosuppressive drugs reshape hepatic immune surveillance and identifies potential strategies to preserve immune competence. These insights provide a basis for optimizing therapeutic regimens, minimizing infection risk, and improving clinical outcomes in patients receiving long-term immunosuppressive treatment.